CONTEMPORARY ISLAMIC EDUCATION: OPPORTUNITIES AND CHALLENGES IN SOCIETY ERA 5.0 - Imam Tabroni; Muhammad Naafi'ul; Nur azizah; Puja Fauzia Rizqita (at-Tahsin, 2022)
This study describes a title of "Contemporary Islamic Education" which begins the important issue of why instruction. Contemporary Islam as far as its origins and its application to the objectives of this study the training needs of Islam are being considered with its Conception and Application. While this examination can provide hypothetical commitments and commitments where hypothetical commitments can be used as another worldview to lead the investigation of contemporary Islamic Education. While grounded commitment, that Islamic schools are very important and agents to be recognized in its origins and contemporary applications today, where this information discipline is consistently advanced, original, created, and at all times and ages. Moreover, this research is a library research. By looking at various literary works related to “Contemporary Islamic Education”, with a focus on writings compiled by specialists of traditional and contemporary Islamic schools. Although the strategy to be used in this examination of course and investigation. These two strategies are not introduced independently, but will be solved independently of the integrated technique used, because in the show it will provide a general representation of the problem to be pondered, then, at that time, of the far-reaching translation information will be held. For a while, scientific strategies are used to see the basic problems that lie behind the problems seen. Information handling methodology using inquiry content.